2022
DOI: 10.1142/s1758825122500508
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Graded Soft Dielectric Elastomer Phononic Crystals: Finite Deformation, Electro-Elastic Longitudinal Waves, and Band Gaps Tunability via Electro-Mechanical Loading

Abstract: Active tuning of elastic wave band gaps received significant attention in the recent past. To this end, soft dielectric elastomers (DEs) have indicated great promise owing to their capability to undergo large reversible deformations and deformation-dependent constitutive properties. In this paper, we investigate the longitudinal wave band gaps an infinite periodic soft functionally graded dielectric elastomer subjected to electro-mechanical biasing fields. Material properties of the functionally graded DE are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Some properties of DE tubes, such as being less bulky and more adaptable to be used in diverse applications, endow DE tubes with priority over different geometries like planar DE actuators [15][16][17]. Other studies suggested that the DE can be operated as tunable phononic crystals to design the DE wave devices with tunable band structures [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Some properties of DE tubes, such as being less bulky and more adaptable to be used in diverse applications, endow DE tubes with priority over different geometries like planar DE actuators [15][16][17]. Other studies suggested that the DE can be operated as tunable phononic crystals to design the DE wave devices with tunable band structures [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the research into architected metamaterials is considerable and rapidly increasing, there are still some limitations, such as the lack of low-frequency bandgaps and tunability. In fact, low-frequency noise and vibration bring new challenges in newly developed technologies [ 7 ], and the design of architected structures to control these harmful vibrations from the propagation pathway over the structural design has become a significant research topic [ 11 , 12 , 13 ]. In addition, clear links have been established between excessive exposure to industrial noise and adverse health effects, such as hearing loss, pain, disrupted sleep cycles, cardiovascular disorders, and impaired cognitive development of workers and labourers in transport and construction, natural resources, and related production occupations [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zeeshan et al [36] demonstrated that the magneto-tunability of phononic bandgaps in a periodic hard-magnetic soft laminated composite and found that the first bandgap width was maximized when the volume fraction of the hard phase exceeded that of the soft phase. Furthermore, Alam et al [37] designed highly nonlinear isolators and diodes for the clean separation of highly deformable solitary waves by using highly deformable metamaterials.…”
Section: Introductionmentioning
confidence: 99%